Sustainable cruise ship tourism : a carrying capacity study for Ísafjörður, Iceland - O'Brien, Megan Anne, 1989- (2014)
Læst til 31.5.2015 Ísafjörður is the principal town of the Westfjords peninsula, Iceland, and it is located on an isthmus in Skutulsfjörður. High-tech industries and research, based on the knowledge and tradition of the fisheries have developed in Ísafjörður, plus numerous new opportunities, predominantly in the rapidly growing sector of tourism. Cruise tourism is nascent in the circumpolar north and communities have the opportunity to guide growth and ensure cruise tourism is and remains sustainable. The number of cruise ships to Ísafjörður has increased steadily since 1996, when only 3 ships arrived in Ísafjörður, in 2013 it is more than 12 times that number and the number of passengers has increased over 2200%. The purpose of this project is to conduct a carrying capacity study, to examine conflicts and quantify the effect of tourism on the local community. This was done through stakeholder interviews, and resident questionnaires. Residents are generally satisfied with the pace of cruise tourism growth and consider it to be an important part of the economy. Cruise ships benefit the community in the social, development and economic areas; however, the environment is the area of most concern for all residents. The locals indicate the benefits have been accumulating over the years and the current point may be the greatest difference between benefits and costs, which is driving cruise tourism through the development stage. Limits have not been reached yet and services are the short-term limiting factor, however, mass tourism is rapidly approaching. Based on these values, assets and imitations, a local action plan is recommended in order to help the municipality proactively manage the growing cruise industry in a way that maintains social, economic and environmental health. Ísafjörður er fjölmennasti þéttbýliskjarninn á Vestfjörðum og er staðsettur í Skutulsfirði. Hátækni iðnaður og rannsóknir byggðar á reynslu sem og þekkingu í fiskveiðum hafa skapast á Ísafirði, auk fjölda annarra tækifæra þá sérstaklega í ...